2022
DOI: 10.1007/s00217-022-04138-0
|View full text |Cite
|
Sign up to set email alerts
|

Amino acids and glycation compounds in hot trub formed during wort boiling

Abstract: The aim of this study was to investigate the amino acid composition and the amount of individual glycation compounds in hot trub formed during boiling of wort prepared from different malts. Compared to the initial amino acid composition of the used malts, some Maillard reaction products (namely MG-H1, pyrraline) and hydrophobic amino acids (leucine, isoleucine, valine, phenylalanine) accumulated in the hot trub, whereas hydrophilic amino acids remained in the boiled wort. For MG-H1, a threefold increase was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…To avoid overestimation of amino acids by hydrolytic cleavage of unstable amino acid modifications, the samples were additionally hydrolyzed enzymatically. , To counteract the incomplete release of amino acids during enzymatic hydrolysis and to compare between acid and enzymatic hydrolysis, we normalized the amino acid contents to an internal reference amino acid measured after enzymatic hydrolysis. , Thus, differences in the hydrolysis yields of different samples can be considered, and corrected absolute contents of the amino acids can be calculated with the use of the absolute amino acid content calculated from acid hydrolysis. For the choice of the reference amino acid, we made a few assumptions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To avoid overestimation of amino acids by hydrolytic cleavage of unstable amino acid modifications, the samples were additionally hydrolyzed enzymatically. , To counteract the incomplete release of amino acids during enzymatic hydrolysis and to compare between acid and enzymatic hydrolysis, we normalized the amino acid contents to an internal reference amino acid measured after enzymatic hydrolysis. , Thus, differences in the hydrolysis yields of different samples can be considered, and corrected absolute contents of the amino acids can be calculated with the use of the absolute amino acid content calculated from acid hydrolysis. For the choice of the reference amino acid, we made a few assumptions.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it represents the protein as a whole. In the past, the amino acids leucine , and alanine were used for this purpose depending on the suitability in the specific case. In our case, it has been shown that alanine fulfills the set requirements best.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation